Employee Empowerment and Technology-Driven Customer Relationship Management: Enhancing Brand Management in the FMCG Sector through SEM-SVM Analysis - Anwar, Rana Salman; Ahmed, Rizwan Raheem; Parmar, Vishnu; Androniceanu, Armenia (Transformations In Business & Economics, 2025)
This study investigates the relationships between employee empowerment, technology-driven customer relationship management (CRM), intelligence generation, organizational responsiveness, and brand management within Pakistan’s Fast-Moving Consumer Goods (FMCG) sector. It explores how these factors influence each other and contribute to organizational success in a highly competitive market environment. Method: A quantitative approach was used with a sample of 356 employees from various FMCG organizations in Pakistan. Data were collected through a structured survey, and the measurement scales were adapted from established research. SEM-SVM, a Structural Equation Modelling and Support Vector Machine, was used for analysis using ADANCO and JASP software. The model assessed both the measurement and structural relationships among the variables. Findings: The findings reveal significant positive relationships between employee empowerment, technology-driven CRM, and organizational responsiveness, all contributing to enhanced brand management. Intelligence generation plays a pivotal role in boosting responsiveness and brand performance. Additionally, SVM analysis supports these results, showing substantial predictive accuracy (R² = 0.739, MAPE = 9.27%) for employee empowerment and responsiveness as key drivers of brand success. These insights highlight the critical importance of empowered employees and advanced CRM systems for FMCG sector success. Originality/Implications: This research offers novel insights into integrating employee empowerment and technology in CRM strategies within FMCG organizations in Pakistan. The implications emphasize the importance of fostering an empowered workforce and leveraging technology to enhance customer relationships and brand management strategies.